Headache Characteristics and Clinical Features of Elderly Migraine Patients. Issue 4 (13th December 2017) - de Rijk, Pablo; Resseguier, Noémie; Donnet, Anne
Abstract : Objective: To investigate the headache characteristics and clinical features of elderly migraine patients at a tertiary headache center. Methods: We retrospectively reviewed 239 records of migraine patients, over the age of 64 at the first visit, who had migraine as defined by the International Classification of Headache Disorders 3rd edition (beta version) from 2006 to 2015 based on the Marseille registry at Timone Hospital. Results: 13.8% (33/239) patients had migraine with aura only, 13.0% (31/239) had both diagnoses. Of the patients who presented with migraine with aura, 13.4% (32/239) presented with aura without headache. Unilateral pain location was reported by 58.6% (140/239) of patients and the throbbing type of pain was present in 50.2% (120/239) of our study group. Photo‐ and phonophobia were observed in 77.4% (185/239) and 79.5% (190/239) of patients. Seventy‐nine out of 239 (30.1%) patients were found to have probable medication overuse. Within this group, 31.65% (25/79) overused triptan and 70.9% (56/79) overused combination analgesics. We found higher frequencies of migraine for patients whose age at onset of migraine was younger than 18 years, and low frequency migraine was reported more frequently in the later onset group ( P = .0357). Discussion: We assess the headache characteristics of elderly migraine patients who were seen at our tertiary headache center and report the high frequency of probable medication overuse headache in this study group. Finally, we suggest that age of onset is an important factor in the clinical profile of these patients.